ENHANCING CHILDREN’S ARTISTIC CREATIVITY THROUGH ARTIFICIAL INTELLIGENCE TECHNOLOGY IN CHINESE PRIMARY SCHOOLS (Journal of Digital System Development, 2025)
Existing studies lack discussion on challenges in fostering Chinese children's artistic creativity and offer no clear conclusions on AI's impact. This study explores the challenges in cultivating children's artistic creativity in primary schools in China and the impact of digital technology on this process. This study will be conducted through a systematic literature review and induction, current problems will be analysed, strategies will be proposed from a theoretical perspective, and future development trends will be analysed. The finding reveals that through a scoping review of 16 relevant studies, it was found that AI technology plays three leading roles in enhancing children's artistic creativity: as a tool, tutor, and medium. AI as a tool helps generate creative ideas, as a tutor provides guidance and support, and as a medium facilitates learning and collaboration. The study highlights the significant role of AI in stimulating children's interest and enhancing their artistic creativity while noting potential risks, such as increased cognitive load and copyright issues. The research concludes that while digital technology, especially AI, offers substantial benefits for children's artistic creativity, its application requires careful consideration of pedagogical strategies and ethical issues. Future research should continue to explore the effective integration of AI in art education to enhance children's creative abilities.